A papír kékre vált - Muntean, Radu (Romania, 2006)
This film takes viewers back to the days of chaos, uncertainty and scaremongering during the Romanian regime-change and liberation. On December 22, 1989 an armored unit is patrolling the outskirts of the city when they hear that “terrorists” are attacking the television headquarters which has actually been occupied by the insurgents. Reception is so bad that they do not understand what is going on, but they can suspect that the Ceauşescu regime is about to end. One of the privates absconds to join the insurgents and his comrades dutifully set out to find him. The film is a mosaic of a frenzied night in which soldiers receive their commands on television from poets and actors, the radio broadcasts fake messages, arms are distributed by civilians and Roma are arrested because they are mistaken for Arab terrorists.
Keywords: Fiction films